Likeness Is in the Eye of the Beholder: Byzantine Portraiture in Art Historiography and Byzantine Perception - Adashinskaya, Anna (Actual Problems of Theory and History of Art, 2022)
The present paper addresses the problem of likeness in Byzantine donor portrait and treats this issues, initially, in the context of the historiography of Byzantine portraiture and, further, in the contemporary Byzantine sources, the epigrams by the Palaiologan poet Manuel Philes. It looks at two consecutive methodological trends in the Byzantine portrait historiography: the first, traditional art historical, investigates the portraits as objects, i.e. it treats their style, iconography, and historical context; the second, stemming from the cultural studies, discusses the engagement of the viewer with the images and the process of beholding as performative in its nature. To understand the problem of likeness in this context, the article turns to the problem of art beholding in the Byzantine sources. Namely, it follows the description of viewers’ experience in the texts that accompanied works of art, inscriptional epigrams, and finds that an image was perceived as paradoxical by its nature, being simultaneously extremely resemblant of natural phenomena and lacking the ability of speech. The research proceeds to investigate two examples of preserved Byzantine portraits accompanied by epigrams in situ (Portrait of Niphon at the Christ Church in Mborje and the portrait of Demetrios Phatmeris at the St. Panteleimon in Ohrid). It finds that the texts and images proposed to the beholders the different types of information which affected the viewer synergistically and provoked his/her emotional response. The final part of the paper deals with two epigrammatic epitaphs by Manuel Philes (To a megas stratopedarches and To Saponopoulos) and inquires into the strategies developed to facilitate the communication between the images and beholders. It concludes that the recognition of the’ personalities of the deceased was achieved through emotional engagement with the read or pronounced texts and, theoretically, the observed images. In this framework, the likeness was the matter of the beholder’s ability to sympathize with the deceased and to assist with prayers into his/her future salvation.This article is part of a project Art Historiographies in Central and Eastern Europe. An Inquiry from the Perspective of Entangled Histories (ArtHistCEEStG–802700) that has received funding from the European Research Council (ERC) under the European Union’s Starting Grant Horizon 2020 research and innovation program.
Keywords: Byzantine donor portrait; Byzantine funeral portrait; historiography; art history; Byzantine studies; portrait iconography; performative turn; epitaphs; Manuel Philes; beholder; inscriptions; art epigrams